3D Printing to Model Surgical Repair of Complex Congenitally Corrected Transposition of the Great Arteries. Issue 3 (May 2019) - Sahayaraj, R. Anto; Ramanan, Sowmya; Subramanyan, Raghavan; Cherian, Kotturathu Mammen
We report the use of three-dimensional (3D) modeling to plan surgery for physiologic repair of congenitally corrected transposition of the great arteries with pulmonary atresia, dextrocardia, and complex intra cardiac anatomy. Based on measurements made from the 3D printed model of the actual patient's anatomy, we anticipated using a composite valved conduit (Dacron tube graft, decellularized bovine jugular vein, and aortic homograft) to establish left ventricle-to-pulmonary artery continuity with relief of stenosis involving the pulmonary artery confluence and bilateral branch pulmonary arteries.